2000
DOI: 10.1007/s004640000257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 pneumoperitoneum on early cellular markers of retinal ischemia in rabbits with α-chymotrypsin–induced glaucomarid=""id=""Presented in abstract form at the annual meeting of the Société Française d'Anesthésie-Réanimation, Paris, France, September, 1999, and the annual meeting of the European Society of Anaesthesiologists, Vienna, Austria, 2000 April

Abstract: In rabbits with alpha-chymotrypsin-induced glaucoma, a 4-h CO(2) pneumoperitoneum of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, intraocular pressure significantly increased with PNP in the head-down position, although it remained within the diurnal range [ 143 ]. A subsequent study did not observe any differences in terms of retinal layer organization and the distribution of intracellular vimentin and actin [ 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, intraocular pressure significantly increased with PNP in the head-down position, although it remained within the diurnal range [ 143 ]. A subsequent study did not observe any differences in terms of retinal layer organization and the distribution of intracellular vimentin and actin [ 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to those in other reports. 12,13 The increase in IOP was directly related to MAP in our patients. The etiology of perioperative visual loss is thought to be directly influenced by alterations in ocular perfusion pressure from changes in MAP and to be indirectly related to IOP elevation.…”
Section: Discussionmentioning
confidence: 55%
“…Many of the studies highlighting POVL and markedly elevated IOP changes (reaching glaucomatous range) after laparoscopic surgery had been performed with steep Trendelenburg position or in prolonged procedures. 1214,19,21,22,24,25 Mondzelewski et al 22 observed a significantly elevated IOP in patients undergoing robot-assisted laparoscopic procedures in steep Trendelenburg position compared with IOP in those undergoing laparoscopy or open procedures in a horizontal position, further highlighting the role of positioning over and above that of pneumoperitoneum in significant IOP elevations. A recent study performed among patients undergoing laparoscopic colorectal surgery showed greater IOP elevation in both eyes of patients in Trendelenburg position during the surgical procedure, but found no substantial difference between the Trendelenburg and non-Trendelenburg group when IOP was measured 48 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation